2015
DOI: 10.1177/0310057x1504300504
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Function, Quality of Life and Mental Health in Survivors of Out-of-Hospital Cardiac Arrest: A Review

Abstract: There is growing interest in the long-term outcomes of patients surviving out-of-hospital cardiac arrest (OHCA). This paper aims to summarise the available literature on the long-term cognitive, health-related quality of life (QoL) and mental health outcomes of survivors of OHCA. Between 30 and 50% of survivors of OHCA experience cognitive deficits for up to several years post-discharge. Deficits of attention, declarative memory, executive function, visuospatial abilities and verbal fluency are commonly report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0
14

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(90 citation statements)
references
References 54 publications
4
72
0
14
Order By: Relevance
“…Similarly, for adults after out-of-hospital CA, memory is the domain most significantly affected, although executive functioning, fine motor, and visuospatial skills are also adversely affected. [6][7][8][9][10][11] We found the greatest impairment based on measures of visual memory, with relatively less impairment based on verbal memory measures; this pattern (greater visual relative to verbal memory impairment) has previously been reported for survivors of pediatric CA. 22 In this population, individualized neuropsychological assessment can guide appropriate cognitive rehabilitation and educational services, especially for older children.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Similarly, for adults after out-of-hospital CA, memory is the domain most significantly affected, although executive functioning, fine motor, and visuospatial skills are also adversely affected. [6][7][8][9][10][11] We found the greatest impairment based on measures of visual memory, with relatively less impairment based on verbal memory measures; this pattern (greater visual relative to verbal memory impairment) has previously been reported for survivors of pediatric CA. 22 In this population, individualized neuropsychological assessment can guide appropriate cognitive rehabilitation and educational services, especially for older children.…”
Section: Discussionsupporting
confidence: 56%
“…For adult out-of-hospital CA survivors, memory is most impaired, and deficits in executive functioning, fine motor skills, and visuospatial skills are often present. [6][7][8][9][10][11] Because these specific domains of neuropsychological functioning are not as well developed or readily testable in young children, we describe neuropsychological outcomes separately for younger and older children. The goal of the present study is to provide novel information about the spectrum of neuropsychological outcomes of children after CA by age group and more precisely delineate neuropsychological functioning of children in both age groups classified as having favorable outcomes.…”
mentioning
confidence: 99%
“…These results are similar to those reported in smaller studies from Sweden, Canada, and the Netherlands, and it is reasonable to conclude that the majority of survivors after OHCA are independent, able to return to work and maintain a good QoL [62][63][64][65]. Another important factor that may lead to impaired QoL and functional outcome is fatigue, which has been reported in a high proportion of survivors of OHCA [66].…”
Section: Quality Of Life and Activities Of Daily Livingsupporting
confidence: 87%
“…However, the study was not powered to assess cognitive outcomes and results need to be interpreted with caution [13]. Nonetheless, this study reinforces the fact that severe neurological impairment is rare among survivors of cardiac arrest, but cognitive dysfunction may be underestimated given limitations in study design including standardized neuropsychological testing [55,66].…”
Section: The Effect Of Targeted Temperature Management On Cognitive Amentioning
confidence: 72%
“…While the patients' respiratory symptoms had largely improved, they still suffered from significant weakness and fatigue, with persistent limitations in their functional state at five years 7 . In this issue, Green et al present a review of functional outcomes for survivors of those who suffered an out-of-hospital cardiac arrest 8 . They showed that almost half of all survivors had cognitive impairment and mental health issues.…”
Section: Goals Of Therapy: Should We Ask What Our Patients Really Want?mentioning
confidence: 99%